Level Of Depression And Quality Of Life Among Caregivers Of Cancer Patients: Hospital-Based Study - Ali, Umaira; Sabir, Syed Arshad; Khalid, Kanwal; Iram, Rabia (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the level of depression and quality of life among caregivers of patients with cancer. Methods: It was a descriptive cross-sectional study done at the NORI hospital in Islamabad from April 2020 to October 2020. A total of 150 study participants were selected by a purposive sampling technique. The questionnaire consists of a Sociodemographic profile of caregivers, including age, gender, marital status, occupation, relationship to patient, education, duration of caregiving, stage of the cancer of the patient, and type of cancer. To measure participants’ quality of life ‘caregiver quality of life-cancer index’ was used. The CQOLC is a self-administered scale specifically designed to evaluate cancer patient caregiver quality of life. To measure participants’ depression, the Beck depression inventory scale was used. Results: In this study, 44% of caregivers were under 50years, 70% were female, 88% were married, 44.7% were housewives, and 56% were secondary school graduates. 85 caregivers had been caring for the patient for over a year. 37.3% were the parents of the caregivers. 49.3% were patients with cancers of the reproductive system, and 81 had stage 3 cancer. Mean score of CQOLC (caregiver quality of life index cancer) is 80.625± 3.422, median 80, and range 72-87. 73 (48.7%) showed poor quality of life. Mean score of BDI (beck depression inventory) for depression is 24.4733± 4.877, median (range) 24(19-39). 132 (88%) showed moderate to severe depression. This study showed a significant association of depression with age, gender, relation with the patient, type of cancer, and stage of cancer (P<O.05). Similarly, quality of life has shown an association with age, gender, relationship with the patient, and duration of caregiving (P<0.05). Conclusion: The results showed that caregivers’ quality of life is affected, and they had mild to moderate depression. Key words: cancer, caregiver, depression, quality of life